2021
DOI: 10.1111/ijlh.13554
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy study of a novel alternate method measuring erythrocyte sedimentation rate for prototype hematology analyzer Celltac α+

Abstract: Introduction The erythrocyte sedimentation rate (ESR) is a nonspecific inflammation indicator. In laboratory testing, automated ESR analyzers may use the reference Westergren method (Reference WG), modified Westergren (Modified WG), or Alternate ESR method (Alternate ESR) based on photometric rheology. A prototype hematology analyzer Celltac α+ (Nihon Kohden Corporation) with built‐in Novel ESR analysis technology (Novel ESR) was developed to improve the accuracy of Alternate ESR. Alternate ESR uses only the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In addition, the device can simultaneously measure the syllectogram and CBC in a few minutes, making it suitable for our ESR estimation methods that require the Ht. The clinical performance of a rapid ESR measuring system using a similar method had been evaluated prior to this report [ 40 ]. In the present study, we clarified the details of the method for calculating the sedimentation rate using the HAI with the optimal measurement time and modified Stokes’ law.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the device can simultaneously measure the syllectogram and CBC in a few minutes, making it suitable for our ESR estimation methods that require the Ht. The clinical performance of a rapid ESR measuring system using a similar method had been evaluated prior to this report [ 40 ]. In the present study, we clarified the details of the method for calculating the sedimentation rate using the HAI with the optimal measurement time and modified Stokes’ law.…”
Section: Resultsmentioning
confidence: 99%
“…The 342 samples (covering HTV and LTV) from different departments were selected for comparability evaluation of ESR. The results suggested that the ESR test results of the BC‐720 hematology analyzer had a good correlation with that of the Westergren method, and were superior to most of the similar products reported so far 30,32–34 . Passing–Bablok regression analysis showed that BC‐720 hematology analyzer ( Y = 2.082 + 0.9869 X , r = 0.9657, n = 342) had a better correlation with Westergren method that TEST 1 ( Y = 1.436 + 1.366 X , r = 0.8665, n = 334).…”
Section: Discussionmentioning
confidence: 77%
“…ESR is the result of the interaction of multiple substances, and the common ESR influencing factors are mainly most substances such as HCT, Fbg, GLB, and ALB 30,34 ; the analytical results of the above four types of abnormal samples showed that the BC‐720 ESR results all correlated well with the Westergren method, indicating that it has certain antiinterference ability.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations